THE INFLUENCE OF VILLAGE APARATORS COMPETENCY ON THE QUALITY OF VILLAGE FINANCIAL STATEMENTS - Ayie Srie Yuniawati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine the Village Apparatus Competence, the Quality of Village Financial Statements and the Effect of Village Apparatus Competence on the Quality of Village Financial Statements in Sumedang Selatan District, Sumedang Regency. This research is included in survey research with a sample of 50 village officials. The data analysis method used is simple linear regression analysis. The results obtained from this study indicate that: (1) Village officials in Sumedang Selatan District, Sumedang Regency can be said to be competent; (2) The village financial reports in Sumedang Selatan Subdistrict, Sumedang Regency can be said to be of quality; (3) Village Apparatus Competence (X) has a positive and significant effect on the Quality of Village Financial Statements (Y) in Sumedang Selatan sub-district, Sumedang district. The results of hypothesis testing with t test show tcount> ttable (3.134> 2.00856) and have a determination coefficient value of 11.03% with a significance of 0.004